BUSINESS PROCESS MODELING, SYSTEM ENGINEERING AND THEIR APPROACH TO ITS APPLICATION IN INDUSTRIAL CAPACITY (Balkan Journal of Applied Mathematics and Informatics, 2022)
Abstract. Most enterprises have a pretty good idea of the various business processes powering their daily operations. However, when they need to ensure that those processes consistently drive optimal outcomes, “a pretty good idea” isn’t enough. The primary objective of business process modeling tools is to analyze how things are right now and simulate how should they be carried out to achieve better results. If an organization wants research and development (R&D) investments to produce sufficient returns, IT issues resolved with minimal downtime or a highly accurate lead qualification workflow, it needs to understand these processes on an objective and comprehensive level. Even the business users directly involved in these processes may lack total transparency into exactly what happens at every step of the way.
Keywords: Business analysts; business process management (BPM); Process models; Systems Engineering